Impediments to Growth of the Garment and Food Industries in Cambodia: Exploring Potential Benefits of the ASEAN-PRC FTA - Vannarith Chheang; Shintaro Hamanaka (Asian Development Bank (ADB), 2011)
This paper attempts to identify structural constraints to growth and exports within Cambodia's key industries and to consider the policy actions needed to reduce obstacles to trade. The paper places special emphasis on Cambodia's exports to the People's Republic of China (PRC), given the major export opportunities arising from the free trade agreement (FTA) between the Association of Southeast Asian Nations (ASEAN) and the PRC, known as the ASEAN–[People's Republic of] China FTA (ACFTA). A qualitative case study method was applied at the firm-level by conducting face-to-face interviews to identify the impediments to the growth and exports of key industries in Cambodia, and to examine the opportunities and challenges presented by the ACFTA. This study covers the garment and food industries, which are critical to the economic development of Cambodia in the context of regional and global economic integration. The food industry, with its large number of small and medium-sized enterprises, has great potential for contributing to pro-poor growth in Cambodia, while the textile industry is the largest employer in the Cambodian labor force and is critical for poverty reduction efforts through export-led growth. The study also provides policy recommendations at both the industry and government levels.
hdl:11540/2009
Keywords: F13; F14; F15; 330; Cambodian economy; garment industry; food industry; ASEAN-[People's Republic of] China FTA; firm-level analysis; bribery